Analysis of English-Spanish False Friends - Inčiuraitė-Noreikienė, Lina; Šarkaitė, Deimantė (Verbum, 2022)
The present study aims to carry out an analysis of English-Spanish false friends in order to establish the most prevailing type of false friends and to determine their degree of falseness and semantic resemblance. Qualitative and quantitative methods were used to conduct the research. The results of the analysis have shown that the most dominant part of speech among false friends in English and Spanish is the category of nouns. The vast majority of false friends share their origins in Latin. The most prevailing type of false friends is semantic total. The data gathered from the questionnaire display that the majority of language users are familiar with the phenomenon and can recognize and understand the meaning of the false friend word pairs.